2020
DOI: 10.26508/lsa.202000865
|View full text |Cite
|
Sign up to set email alerts
|

Proteostasis in dendritic cells is controlled by the PERK signaling axis independently of ATF4

Abstract: In stressed cells, phosphorylation of eukaryotic initiation factor 2α (eIF2α) controls transcriptome-wide changes in mRNA translation and gene expression known as the integrated stress response. We show here that DCs are characterized by high eIF2α phosphorylation, mostly caused by the activation of the ER kinase PERK (EIF2AK3). Despite high p-eIF2α levels, DCs display active protein synthesis and no signs of a chronic integrated stress response. This biochemical specificity prevents translation arrest and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 87 publications
(151 reference statements)
2
17
0
Order By: Relevance
“…Our BMDC studies showed that antigen pulsing selectively activates IRE1α but not PERK or ATF6, excluding the standard UPR as a key mechanistic driver. This contrasts with plasmacytoid DCs (pDCs), which do not mediate cross-presentation, and interestingly display constitutive activation of PERK (Mendes et al, 2021). BMDC pulsing with different protein antigens, or with lysates of several cancer cell lines, induced significant levels of IRE1α activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our BMDC studies showed that antigen pulsing selectively activates IRE1α but not PERK or ATF6, excluding the standard UPR as a key mechanistic driver. This contrasts with plasmacytoid DCs (pDCs), which do not mediate cross-presentation, and interestingly display constitutive activation of PERK (Mendes et al, 2021). BMDC pulsing with different protein antigens, or with lysates of several cancer cell lines, induced significant levels of IRE1α activity.…”
Section: Discussionmentioning
confidence: 99%
“…IRE1 via XBP1s controls eosinophil, DC, and plasma cell development (Reimold et al, 2001;Iwakoshi et al, 2007;, which contribute to neuroinflammation in MS and Experimental Autoimmune Encephalomyelitis (EAE), the mouse model of MS (Greter et al, 2005;Wensky et al, 2005;Mundt et al, 2019;Pröbstel et al, 2020). Furthermore, DCs and plasma cells show constitutive UPR activation and display an elevated protein synthesis rate in steady state (Osorio et al, 2014;Khalsa et al, 2019;Mendes et al, 2020). In these cell types, XBP1s maintains ER architecture, whereas RIDD controls functional aspects, including antigen cross-presentation and cDC1s survival, or immunoglobulin production by plasma cells (Benhamron et al, 2014;Osorio et al, 2014;Tavernier et al, 2017).…”
Section: The Upr In Immune Cell Function In Physiological and Inflammatory Statesmentioning
confidence: 99%
“…In these cell types, XBP1s maintains ER architecture, whereas RIDD controls functional aspects, including antigen cross-presentation and cDC1s survival, or immunoglobulin production by plasma cells (Benhamron et al, 2014;Osorio et al, 2014;Tavernier et al, 2017). PERK signaling is also active in DCs (Mendes et al, 2020), whereas ATF6 remains understudied in immunity. These findings suggest that IRE1 and PERK signaling could be targets in neuroinflammatory pathologies involving DCs and plasma cell function, such as EAE (Greter et al, 2005;Mundt et al, 2019;Pröbstel et al, 2020).…”
Section: The Upr In Immune Cell Function In Physiological and Inflammatory Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from acute ER stress, the phosphorylation levels of eIF2α in the spleen and FLT3L BMDCs were significantly increased under steady-state conditions ( Mendes et al, 2021 ). During the DC differentiation process, PERK was activated, which contributed to a high level of p-eIF2α.…”
Section: Endoplasmic Reticulum Quality Control and Immune Cellsmentioning
confidence: 99%